Optimization problems and their applications : 7th International Conference, OPTA 2018, Omsk, Russia, July 8-14, 2018, Revised selected papers /: 7th International Conference, OPTA 2018, Omsk, Russia, July 8-14, 2018, Revised selected papers. (2018) - Unknown
No abstract available